THE PERFORMANCE ANALYSIS OF STFT-ANFIS CLASSIFICATION METHOD ON PULSED RADAR TARGET CATEGORIZATION - Avci, Engin; Turkoglu, Ibrahim; Poyraz, Mustafa (Istanbul Univ, Fac Engineering, 2006)
In this paper, a pattern recognition system is developed for automatic classification of the radar target signals. Feature extraction is an important subset of the pattern recognition system. For feature extraction is used Short Term Fourier Transform (STFT) time-frequency distribution of the pulse radar target signals. Adaptive Network Based Fuzzy Inference System (ANFIS) classifier is used at classifier part of the pattern recognition system. Radar signals are obtained from pulse radar system for various targets. The classifier performance is evaluated according to the proposal method.
Keywords: Feature extraction; ANFIS; radar target classification; STFT